2005
DOI: 10.1016/j.jcf.2005.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Lung transplantation for cystic fibrosis: 6-year follow-up

Abstract: Lung transplantation is currently the most effective means of improving survival and quality of life in patients with end-stage cystic fibrosis. In reviewing our 6-year experience we sought to evaluate complications and survival after sequential bilateral lung transplantation. Between October 1996 and October 2002, 114 patients with cystic fibrosis were referred to us from 15 Italian regional centers and 2 support centers for cystic fibrosis as possible candidates for lung transplantation. Of these 114 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 24 publications
2
29
1
Order By: Relevance
“…The Aspergillus-positive and -negative groups were fairly equivalent with regard to age and gender distribution, and no difference in % predicted FEV 1 was observed between them. Furthermore CF patients with respiratory cultures positive for Aspergillus species did not appear to be at an increased risk for complications from lung transplantation (194), although other authors have noted anastomotic dehiscence due to Aspergillus in this setting (249,473). On the other hand, Shoseyov and colleagues reported six CF patients with sputum cultures that grew A. fumigatus and who experienced pulmonary exacerbations (542).…”
Section: Aspergillus Speciesmentioning
confidence: 98%
“…The Aspergillus-positive and -negative groups were fairly equivalent with regard to age and gender distribution, and no difference in % predicted FEV 1 was observed between them. Furthermore CF patients with respiratory cultures positive for Aspergillus species did not appear to be at an increased risk for complications from lung transplantation (194), although other authors have noted anastomotic dehiscence due to Aspergillus in this setting (249,473). On the other hand, Shoseyov and colleagues reported six CF patients with sputum cultures that grew A. fumigatus and who experienced pulmonary exacerbations (542).…”
Section: Aspergillus Speciesmentioning
confidence: 98%
“…Indeed, chronic renal failure has been shown to be the most frequent non-infectious medical complication after lung transplantation [12]. Bech et al also showed an early and important decrease in measured glomerular filtration rate in transplanted patients [13].…”
Section: Introductionmentioning
confidence: 99%
“…Several works support a significant association of P. jirovecii colonization with diverse chronic pulmonary diseases (6,12,21). Few severe PcP cases in cystic fibrosis (CF) patients have been reported (23,25), and only some studies have reported Pneumocystis carriage, the clinical significance of which remains practically unexplored (14,(18)(19)(20)(22)(23)(24)(25)(26). The aims of the present study were therefore to evaluate the prevalence of P. jirovecii colonization during a prospective multicenter observational study, to provide information regarding the distribution of Pneumocystis genotypes, and to explore the clinical relevance of Pneumocystis colonization among CF patients in France.…”
mentioning
confidence: 96%